Perturbed autophagy intervenes systemic lupus erythematosus by active ingredients of traditional Chinese medicine - Tian, Rui; Yuan, Lin; Huang, Yuan; Zhang, Rui; Lyu, Hao; Xiao, Shuai; Guo, Dong; Ali, Declan William; Michalak, Marek; Chen, Xing-Zhen; Zhou, Cefan; Tang, Jingfeng (Frontiers in Pharmacology, 2023)
Systemic lupus erythematosus (SLE) is a common multisystem, multiorgan heterozygous autoimmune disease. The main pathological features of the disease are autoantibody production and immune complex deposition. Autophagy is an important mechanism to maintain cell homeostasis. Autophagy functional abnormalities lead to the accumulation of apoptosis and induce the autoantibodies that result in immune disorders. Therefore, improving autophagy may alleviate the development of SLE. For SLE, glucocorticoids or immunosuppressive agents are commonly used in clinical treatment, but long-term use of these drugs causes serious side effects in humans. Immunosuppressive agents are expensive. Traditional Chinese medicines (TCMs) are widely used for immune diseases due to their low toxicity and few side effects. Many recent studies found that TCM and its active ingredients affected the pathological development of SLE by regulating autophagy. This article explains how autophagy interferes with immune system homeostasis and participates in the occurrence and development of SLE. It also summarizes several studies on TCM-regulated autophagy intervention in SLE to generate new ideas for basic research, the development of novel medications, and the clinical treatment of SLE.